Intravital placenta imaging reveals microcirculatory dynamics impact on sequestration and phagocytosis of Plasmodium-infected erythrocytes. - Luciana Vieira de Moraes; Carlos Eduardo Tadokoro; Iván Gómez-Conde; David N Olivieri; Carlos Penha-Gonçalves (PLoS Pathogens, 2013)
Malaria in pregnancy is exquisitely aggressive, causing a range of adverse maternal and fetal outcomes prominently linked to Plasmodium-infected erythrocyte cytoadherence to fetal trophoblast. To elucidate the physiopathology of infected erythrocytes (IE) sequestration in the placenta we devised an experimental system for intravital placental examination of P. berghei-infected mice. BALB/c females were mated to C57Bl/6 CFP+ male mice and infected with GFP+ P. berghei IE, and at gestational day 18, placentas were exposed for time-lapse imaging acquisition under two-photon microscopy. Real-time images and quantitative measurements revealed that trophoblast conformational changes transiently restrain blood flow in the mouse placental labyrinth. The complex dynamics of placental microcirculation promotes IE accumulation in maternal blood spaces with low blood flow and allows the establishment of stable IE-trophoblast contacts. Further, we show that the fate of sequestered IE includes engulfment by both macrophagic and trophoblastic fetal-derived cells. These findings reinforce the current paradigm that IE interact with the trophoblast and provide definitive evidence on two novel pathogenesis mechanisms: (1) trophoblast layer controls placental microcirculation promoting IE sequestration; and (2) fetal-derived placental cells engulf sequestered IE.